PENGARUH KOMPENSASI FINANSIAL DAN PENGEMBANGAN KARIR TERHADAP TURNOVER INTENTION DENGAN KEPUASAN KERJA SEBAGAI VARIABEL INTERVENING - Wawan Prahiawan Wawan Prahiawan; Embun Parmanasari Embun Parmanasari (NIAGARA Scientific Journal, 2018)
This study aims to determine the effect of financial compensation and career development on turnover intention through job satisfaction as intervening variable. In this research the method used is descriptive and causal method. Technique of collecting data using questionnaire with likert scale measurement. Determination of samples used slovin formula and obtained a sample of 99 respondents using quantitative data analysis methods. From result of calculation of SPSS v.20, result of research with significance level of 0,05% obtained conclusion: (1) there is negative and significant influence of financial compensation to turnover intention got tcount > ttable (-4.540 > 1.661) and sig value < 0.05 (0.00 < 0.05) (2) there is a negative and significant influence of career development toward intention turnover obtained tcount > ttable (-3.631 > 1.661) and sig value < 0.05 (0.00 < 0.05) (3) there is a positive and significant influence of financial compensation to job satisfaction obtained tcount > ttable (3.433 > 1.661) and sig value < 0.05 (0.01 < 0.05) (4) there is a positive and significant influence of career development on job satisfaction got tcount > ttable (2.431 > 1.661) and sig value < 0.05 (0.017 < 0.05) (5) there is negative and significant influence of job satisfaction toward intention turnover obtained tcount > ttable (-11.023 > 1.661) and sig value < 0.05 (0.00 < 0.05) (6) the job satisfaction variable gives a significant mediation effect of the financial compensation relationship to turnover intention with tcount > ttable (3.416 > 1.661) (7) the job satisfaction variable gives a significant mediation effect of the career development to turnover intention with t-count > t-table (2.502 > 1.661).